The Impact of Talent Management Practices on Organizational and Human Resources Outcomes: A Study on Philippines Department Of Foreign Affairs Talent Management Practices (International Journal of Scientific Research and Management (IJSRM), 2022)
The study examined the Philippine Department of Foreign Affairs (DFA) talent management practices and whether its practices influence its organizational and human resources outcomes. The three independent variables are talent attraction, talent development, and talent retention, while the two dependent variables are organizational and human resources outcomes. Three hundred respondents answered a 43-item questionnaire. The Pearson’s Correlation analysis results show significant positive relationships between organizational outcomes and (a) talent attraction, r=.734, N=300, p < 0.001; (b) talent development, r=.699, N=300, p < 0.001, and (c) talent retention, r=.748, N=300, p < 0.001. Likewise, the analysis showed that there are significant positive relationships between human resource outcomes and (a) talent attraction, r=.753, N=300, p < 0.001; (b) talent development, r=.765, N=300, p < 0.001, and (c) talent retention, r=.808, N=300, p < 0.001. The study revealed that talent attraction, development, and retention positively influence organizational and human resources outcomes. Talent Development is the primary strength of the Department with the highest weighted mean (WM:3.71; SD:0.78), followed by Talent Attraction (WM:3.56; SD:0.81) and talent retention (WM:3.27; SD:0.90).